SUBJEK HUKUM ATAS PELAYANAN KONTRASEPSI DALAM PELAKSANAAN PROGRAM KELUARGA BERENCANA - Joko Nur Sariono (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
Subject Law gave by the authority for contraception service in execution program the KB is doctor and midwife arranged in Regulation of Minister for Public Health R.I. and Rights and obligations in execution of contraception service program the Family Berencana go into effect reciprocally its meaning is rights for health energy represent the obligation of acceptor KB so on the contrary rights for acceptor KB represent the obligation of health energy.